Fish eyes and brain as primary targets for mercury accumulation - a new insight on environmental risk assessment - Pereira, Patrícia
Fish eyes and brain are highly susceptible to environmental Hg exposure but this issue is still scarcely investigated, mainly regarding methylmercury (MeHg) accumulation. Yet, Hg levels in fish lens have not been previously examined under field conditions. Total Hg (tHg), MeHg and inorganic Hg (iHg) levels were assessed in the brain, eye wall and lens of the golden grey mullet (Liza aurata) from an Hg contaminated area, both in winter and summer, together with water and sediment levels. Sampling was performed at Aveiro lagoon (Portugal) where a confined area (LAR) is severely contaminated by Hg. Fish brain, eye wall and lens accumulated higher levels of tHg, MeHg and iHg at LAR than the reference site, reflecting faithfully environmental spatial differences. The brain and eye wall responded also to the winter-summer changes found in water and sediment, accumulating higher levels of MeHg (and tHg) in winter. Contrarily, lens was unable to reflect seasonal changes, probably due to its composition and structural stability over time. The three neurosensory structures accumulated preferentially MeHg than iHg (MeHg was higher than 77% of tHg). Lens exhibited a higher retention capacity of MeHg (mean around 1μgg-1 at LAR), accumulating higher levels than the other two tissues. Interestingly, MeHg and iHg levels were significantly correlated for the brain and eye wall but poorly associated within the two analysed eye components. The high levels of MeHg found in the brain, eye wall and lens could compromise their functions and this needs further research.